Senescence and Immunoregulation in the Tumor Microenvironment - Ruhland, Megan K.; Alspach, Elise (Frontiers in Cell and Developmental Biology, 2021)
Immunotherapies have revolutionized cancer treatment, but despite the many lives that have been extended by these therapies many patients do not respond for reasons that are not well understood. The tumor microenvironment (TME) is comprised of heterogeneous cells that regulate tumor immune responses and likely influence immunotherapy response. Senescent (e.g., aged) stroma within the TME, and its expression of the senescence-associated secretory phenotype induces chronic inflammation that encourages tumor development and disease progression. Senescent environments also regulate the function of immune cells in ways that are decidedly protumorigenic. Here we discuss recent developments in senescence biology and the immunoregulatory functions of senescent stroma. Understanding the multitude of cell types present in the TME, including senescent stroma, will aid in the development of combinatorial therapeutic strategies to increase immunotherapy efficacy.